TRPC3 channels confer cellular memory of recent neuromuscular activity - Rosenberg, Paul (National Academy of Sciences, 2004)
Skeletal muscle adapts to different patterns of motor nerve activity by alterations in gene expression that match specialized properties of contraction, metabolism, and muscle mass to changing work demands (muscle plasticity). Calcineurin, a calcium/calmodulin-dependent, serine–threonine protein phosphatase, has been shown to control programs of gene expression in skeletal muscles, as in other cell types, through the transcription factor nuclear factor of activated T cells (NFAT). This study provides evidence that the function of NFAT as a transcriptional activator is regulated by neuromuscular stimulation in muscles of intact animals and that calcium influx from the transient receptor potential (TRPC3) channel is an important determinant of NFAT activity. Expression of TRPC3 channels in skeletal myocytes is up-regulated by neuromuscular activity in a calcineurin-dependent manner. These data suggest a mechanism for cellular memory in skeletal muscles whereby repeated bouts of contractile activity drive progressively greater remodeling events.